2019
DOI: 10.1111/mmi.14214
|View full text |Cite
|
Sign up to set email alerts
|

Class II contact‐dependent growth inhibition (CDI) systems allow for broad‐range cross‐species toxin delivery within the Enterobacteriaceae family

Abstract: Summary Contact‐dependent growth inhibition (CDI) allows bacteria to recognize kin cells in mixed bacterial populations. In Escherichia coli, CDI mediated effector delivery has been shown to be species‐specific, with a preference for the own strain over others. This specificity is achieved through an interaction between a receptor‐binding domain in the CdiA protein and its cognate receptor protein on the target cell. But how conserved this specificity is has not previously been investigated in detail. Here, we… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
24
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(28 citation statements)
references
References 39 publications
3
24
0
Order By: Relevance
“…B. thailandensis also appears to participate in interspecies interbacterial signaling, responding with gene expression changes to BcpA delivered by B. dolosa (14). Our results are supported by a recent study showing that some CdiA proteins (class II) are capable of mediating interspecies competition between E. coli and other Enterobacteriaceae species (22), suggesting that interspecies CDI may be more widespread than appreciated. Further investigation to determine whether interspecies CDI and/or signaling among Burkholderia species is prevalent is warranted, because these phenomena may have ecological or clinical applications.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…B. thailandensis also appears to participate in interspecies interbacterial signaling, responding with gene expression changes to BcpA delivered by B. dolosa (14). Our results are supported by a recent study showing that some CdiA proteins (class II) are capable of mediating interspecies competition between E. coli and other Enterobacteriaceae species (22), suggesting that interspecies CDI may be more widespread than appreciated. Further investigation to determine whether interspecies CDI and/or signaling among Burkholderia species is prevalent is warranted, because these phenomena may have ecological or clinical applications.…”
Section: Discussionsupporting
confidence: 84%
“…We also demonstrate that B. thailandensis can inhibit the growth of B. multivorans via CDI. Along with a recent study of Enterobacteriaceae species (22), this finding is one of the first reported examples of interspecies CDI.…”
Section: Discussionsupporting
confidence: 60%
“…Beck et al demonstrated that the class II CdiA proteins that bind to OmpF/OmpC are strain-specific and able to discriminate between different strains of E. coli, with a preference for their "own" strain over others [42]. On the contrary, Virtanen et al found, that the E. coli class II CdiA RBDs allow for the delivery of toxic effectors into many different Enterobacteriaceae spp., including Enterobacter cloacae and Enterobacter aerogenes, Klebsiella pneumoniae, and Salmonella typhimurium, suggesting that class II CDI is a broad-range inter-species competition system [46]. Similar findings were made in other works: thus, over-expression of the CdiBAI module in E. cloacae leads to an inhibition of E. coli growth [70], while CDI systems of Burkholderia pseudomallei allows for the delivery of effector protein to the closely related B. thailandensis [57].…”
Section: Interbacterial Antagonismsupporting
confidence: 83%
“…Taking into account the variations in composition, E. coli CdiA proteins are usually divided into five or more classes. Classes I-III are defined by the amino acid sequence of the RBD domain [46], which corresponds to three different types of receptors on the surface of the target cell: BamA (class I), OmpC/OmpF (class II), or Tsx (class III) [34,[40][41][42].…”
Section: "Toxin-on-a-stick": the Structure Of The Cdia Proteinmentioning
confidence: 99%
“…Previous findings suggest that SPI-6 is strongly silenced by H-NS and that only in conditions where H-NS expression is decreased or absent can T6SS activity be observed [32,46]. Other contact-dependent competition systems have been suggested to contribute to kin selection by exclusion of others (by inhibiting the growth of non-self bacteria) [48]. Rhs toxins have also been shown to be important during intestinal colonization [32,49].…”
Section: Discussionmentioning
confidence: 99%